PENGARUH KONFLIK KERJA, STRES KERJA, DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA V (PERSERO) PEKANBARU - Ahmad Yofandi; Nuryanti '; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the effect of labor conflicts, work stress and spirit to employees performance in PT. Perkebunan Nusantara V (Persero) Pekanbaru. The population in this study were all employees of the Executive Office Center at PT. Perkebunan Nusantara V (Persero) Pekanbaru is numbered 335 people. While the sampling technique is done by using the formula slovin thus obtained sample of 77 people. Analysis of data using multiple linear regression with SPSS program. Based on the results of data analysis known that the conflict of work, work stress and morale positive and significant effect on the performance of employees at PT. Perkebunan Nusantara V (Persero) Pekanbaru. Conflict of work positive and significant effect on the performance of employees at PT. Perkebunan Nusantara V (Persero) Pekanbaru. Work stress positive and significant effect on the performance of employees at PT. Perkebunan Nusantara V (Persero) Pekanbaru. Spirit of work positive and significant effect on the performance of employees at PT. Perkebunan Nusantara V (Persero) Pekanbaru. Expected to companies in order to improve the performance of its employees to emphasize to employees that are not being selfish at work, stressed to members that the work is not concerned with the interests of each but to prioritize the interest of the company, stressed the head of the company to be thoughtful and receptive to ideas given by team members then take the best decision for a common goal, and to be open for a good team to be mutually open to each other so that between fellow members can criticize and evaluate the work of the team.Keywords: Conflict, Stress, Spirit, and Performance.